Alkali fusion activated regenerated brick powder geopolymer as well as preparation method and strength calculation method thereof

The recycled brick powder is modified through alkali melt activation technology to improve its active silicon-aluminum content, which solves the problem of limited compressive strength improvement after modification of recycled brick powder, realizes the preparation of high-performance gelling materials, and provides an effective strength calculation method, which promotes the sustainable development of building materials.

CN119874234AActive Publication Date: 2025-04-25ZHEJIANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411971420.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the prior art, the improvement of the compressive strength of recycled brick powder after modification is limited, and the lack of effective strength calculation methods is limited, which limits its potential in construction applications.

Method used

The alkali melt activation technology is used to modify the recycled brick powder. Through the combination of physical modification and chemical modification, the active silicon-aluminum content of the recycled brick powder is significantly improved, and a strength calculation formula is proposed. Combined with the mix ratio design research, the strength of the polymer is predicted.

Benefits of technology

It effectively improves the strength of the ground polymer, reduces carbon emissions, realizes the resource utilization of construction waste, provides a high-performance gelling material, and has a wide application prospect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219579410000031
    Figure BDA0005219579410000031
  • Figure BDA0005219579410000061
    Figure BDA0005219579410000061
  • Figure BDA0005219579410000062
    Figure BDA0005219579410000062
Patent Text Reader

Abstract

The invention discloses an alkali fusion activated regenerated brick powder geopolymer as well as a preparation method and a strength calculation method thereof. The geopolymer comprises the following components in parts by mass: 20-30 parts of water, 3-5 parts of a fluxing agent, 20-60 parts of alkali fusion activated regenerated brick powder, 40-80 parts of a precursor material and 5-7 parts of an alkali activator, the preparation method of the alkali fusion activated regenerated brick powder comprises the following steps: 1) drying the regenerated brick powder in a drying oven, and then grinding the regenerated brick powder until the particle size of the regenerated brick powder meets the requirement; and 2) mixing and stirring the ground regenerated brick powder and a fluxing agent, then calcining the mixture in a muffle furnace, and naturally cooling to obtain the alkali fusion activated regenerated brick powder. The geopolymer is prepared on the basis of the regenerated brick powder, and the purposes of high performance, environmental protection and sustainable development are achieved by optimizing the component mix proportion design and the preparation process. The strength calculation method provided by the invention can effectively predict the strength development of the geopolymer, and has practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to an alkali-melting activated recycled brick powder geopolymer and a preparation method thereof and a strength calculation method thereof. Background Art

[0002] Cement, as a basic material for modern construction, produces a large amount of carbon dioxide emissions during its preparation. This process not only increases the environmental burden, but also exacerbates the problem of global climate change. At the same time, the large-scale stacking of brick dust, as a by-product of building demolition activities, has become a pressing environmental issue. The accumulation of brick dust not only occupies valuable land resources, but also may cause soil and water pollution, posing a threat to the ecosystem.

[0003] In the face of these challenges, the application of recycled brick powder has received widespread attention as a way to reduce environmental impact. Currently, most research and practical applications of recycled brick powder are focused on its use as a recycled aggregate for incorporation into new concrete mixes. However, the potential of recycled brick powder is not limited to being an aggregate substitute. The development of geopolymer materials using recycled brick powder has attracted attention as a sustainable alternative to traditional cement-based products. These geopolymers not only provide a way to utilize waste, but also reduce the carbon footprint associated with conventional cement production. In the prior art, the effects of recycled concrete powder and recycled brick powder on the compressive strength of cement-based materials after modification in different ways. Among them, recycled concrete powder contains calcite, dolomite and a small amount of C 2 S and C 3 S, etc., after modification, the compressive strength of cement-based materials increased by 23.2%. The modification methods include physical modification, chemical modification, thermal modification, carbonization modification and nano-modification. The main mineral component of recycled brick powder is quartz, and it contains a small amount of hematite, albite and muscovite. Currently, there are only studies on physical and chemical modification of brick powder, and the compressive strength of cement-based materials after modification is only slightly increased by 11.6%, which is not as good as the compressive strength of recycled concrete powder after modification. Therefore, it is urgent to carry out systematic research that can effectively improve the activity of recycled brick powder based on the chemical and mineral composition characteristics of recycled brick powder.

[0004] Despite the growing research interest in recycled brick dust geopolymers, there is a significant gap in their strength calculation. The lack of a comprehensive strength calculation method for recycled brick dust geopolymers limits the potential of these materials in construction applications. Summary of the invention

[0005] The purpose of the present invention is to provide an alkali-melting activated recycled brick powder geopolymer and a preparation method thereof and a strength calculation method thereof, which is simple to prepare and easy to use, can make full use of construction waste brick powder for recycling and reuse, and prepare a new type of cementitious material through alkali melting activation technology, effectively improve the strength of the geopolymer, and effectively reduce carbon emissions. The strength calculation formula mentioned in the present invention can be effectively combined with mix design research to predict the strength of the geopolymer, and has broad application prospects and research reference value.

[0006] In view of this, the present invention adopts the following technical solution:

[0007] An alkali-melting activated recycled brick powder geopolymer comprises the following components in parts by weight:

[0008] 20-30 parts of water, 20-60 parts of alkali-melting activated regenerated brick powder, 40-80 parts of precursor material, 5-7 parts of alkali activator;

[0009] Wherein, the alkali-melting activated regenerated brick powder is prepared by the following steps:

[0010] Step a1: drying the recycled brick powder in an oven for at least 24 hours, and then grinding the recycled brick powder until the particle size of the recycled brick powder meets the requirements;

[0011] Step a2: Mix the ground recycled brick powder with the flux and stir, stir evenly, place it in a muffle furnace and calcine it at 200° C. for 6 hours with a heating rate of 20° C. / min, and obtain the alkali-melting activated recycled brick powder after natural cooling.

[0012] Furthermore, in step a1, the flux is 3-5 parts by mass, the recycled brick powder is 20-60 parts by mass, the drying temperature in the oven is 60°C, the time is at least 24 hours, and the particle size requirement is not greater than 0.2 mm. Finer recycled brick powder particle size can make it more active.

[0013] Furthermore, the flux is one of lithium metaborate, barium fluoride and ammonium chloride, and its mass concentration is 20%-40%.

[0014] Furthermore, the silicon dioxide content in the recycled brick powder is not less than 45%.

[0015] Furthermore, the precursor material is one of marble sawdust, steel slag and metakaolin, and its calcium content is not less than 40%.

[0016] Furthermore, the alkaline activator is one of potassium hydroxide, potassium silicate and sodium metasilicate, and its mass concentration is 20%-40%.

[0017] A method for preparing the alkali-melting activated regenerated brick powder geopolymer comprises the following steps:

[0018] Step 1: Mix water and alkali activator evenly to obtain a mixed solution; add the alkali-melting activated regenerated brick powder and the precursor material into a stirring pot, mix and stir them thoroughly to obtain a mixed powder;

[0019] Step 2: Mix and stir the mixed powder and the mixed solution to finally obtain an alkali-melting activated recycled brick powder geopolymer.

[0020] Furthermore, during the mixing and stirring of the mixed powder and the mixed solution:

[0021] Stir slowly for 60 seconds, pause for 15 seconds, scrape the slurry off the wall of the stirring pot, continue to stir quickly for 60 seconds, and finally stir slowly for 30 seconds;

[0022] The stirring speeds of the slow stirring and the fast stirring are 90-100 r / min and 250-260 r / min respectively.

[0023] A strength calculation method for the alkali-melting activated regenerated brick powder geopolymer, the formula for the strength calculation method is:

[0024]

[0025] Where: C is the 28d compressive strength of alkali-melting activated recycled brick powder geopolymer, m s is the mass fraction of the precursor material, m f is the mass fraction of flux, m a is the mass fraction of the alkali activator, T is the calcination temperature, m w is the mass fraction of water, ∑m 固 S is the total mass fraction of alkali-melting activated recycled brick powder, precursor material and alkali activator; 1 , K 1 , K 2 They are correction factors for precursor materials, flux and alkali activator respectively, and their values ​​depend on the specific types of precursor materials, flux and alkali activator.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention adopts innovative alkali melting activation technology, combining physical modification and chemical modification, significantly improving the active silicon and aluminum content of recycled brick powder, and promoting the depolymerization-polycondensation reaction in the subsequent alkali activation step. This not only effectively reduces the stacking problem of waste brick powder and reduces its potential pollution to the environment, but also opens up a new path for the resource utilization of construction waste, realizes the transformation of waste into treasure, and promotes the green and sustainable development of the construction industry.

[0028] 2. The present invention significantly reduces the amount of traditional cement used by converting activated recycled brick powder into high-performance cementitious materials. This revolutionary application not only reduces carbon emissions generated during cement production, but also makes positive contributions to reducing greenhouse gas emissions and addressing climate change, reflecting the concept of green environmental protection.

[0029] 3. The present invention cleverly integrates industrial byproducts such as marble saw mud, steel slag, and kaolin. These materials are not only low in cost, but also use them as raw materials to help reduce the discharge of industrial waste, playing a positive role in environmental protection. This efficient use of resources is both economical and environmentally friendly, achieving a win-win situation in economic and environmental benefits.

[0030] 4. The alkali-melting activated recycled brick powder geopolymer developed by the present invention has broad application prospects. It can not only be widely used in multiple fields such as construction, roads, bridges, etc., but also can bring multiple benefits to these fields such as improving structural strength, extending service life, and reducing maintenance costs, demonstrating its outstanding technical advantages and market potential.

[0031] 5. The operation process of the present invention is simple and the preparation process is easy to master, making industrial production possible. By adding industrial byproducts and alkali activators, not only the performance of the cementitious material is optimized, but also the strength of the final product, alkali-melted activated recycled brick powder geopolymer, is significantly improved, providing strong support for the innovation of building materials.

[0032] 6. The present invention proposes a formula for calculating the strength of geopolymers based on alkali fusion activation. The formula has been rigorously verified by experiments and can accurately and effectively predict the strength development of the alkali fusion activated recycled brick powder geopolymer of the present invention, laying a solid foundation for in-depth research and technological progress in related fields. DETAILED DESCRIPTION

[0033] In order to make the use method and features of the present invention more obvious and easy to understand, the following embodiments are specifically cited for detailed description. The methods of the present invention are all conventional methods in the art unless otherwise specified.

[0034] In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper limit and the lower limit of the range is also specifically disclosed, and the value should not be limited to the upper and lower limits or specific examples.

[0035] The alkali-melting activated regenerated brick powder geopolymer of the present invention comprises the following components in parts by weight:

[0036] 20-30 parts of water, 20-60 parts of alkali-melting activated regenerated brick powder, 40-80 parts of precursor material, 5-7 parts of alkali activator;

[0037] Wherein, the alkali-melting activated regenerated brick powder is prepared by the following steps:

[0038] Step a1: drying the recycled brick powder in an oven at 60° C. for at least 24 hours, and then grinding the recycled brick powder until the particle size of the recycled brick powder is no more than 0.2 mm;

[0039] Step a2: Mix the ground recycled brick powder with the flux and stir, stir evenly, place it in a muffle furnace and calcine it at 200° C. for 6 hours with a heating rate of 20° C. / min, and obtain the alkali-melting activated recycled brick powder after natural cooling.

[0040] Preferably, the flux is any one of lithium metaborate, barium fluoride and ammonium chloride, and the mass concentration thereof is 20%-40%.

[0041] Preferably, the particle size of the recycled brick powder is not greater than 0.2 mm, and the silicon dioxide content is not less than 45%.

[0042] Preferably, the method for preparing alkali-melting activated recycled brick powder comprises:

[0043] Preferably, the precursor material is any one of marble sawdust, steel slag and metakaolin, and the calcium content of the precursor material is not less than 40%.

[0044] Preferably, the alkaline activator is one of potassium hydroxide, potassium silicate and sodium metasilicate, and its mass concentration is 20%-40%.

[0045] Preferably, the method for preparing the alkali-melting activated recycled brick powder geopolymer comprises:

[0046] Step 1: Mix water and alkali activator evenly to obtain a mixed solution; add the alkali-melting activated regenerated brick powder and the precursor material into a stirring pot, mix and stir them thoroughly to obtain a mixed powder;

[0047] Step 2: Mix and stir the mixed powder and the mixed solution to finally obtain an alkali-melting activated recycled brick powder geopolymer.

[0048] Preferably, during the mixing and stirring of the mixed powder and the mixed solution:

[0049] First, stir slowly for 60 seconds, pause for 15 seconds, scrape the slurry on the wall of the stirring pot, continue to stir quickly for 60 seconds, and finally stir slowly for 30 seconds; the stirring speeds of the slow stirring and fast stirring are 90-100 r / min and 250-260 r / min respectively.

[0050] After obtaining the alkali-melting activated recycled brick powder geopolymer, pour it into a 20mm×20mm×20mm mold, demould it after 24 hours and cure it under standard conditions for 28 days, and test its compressive strength.

[0051] To make the contents of the present invention easier to understand, the technical solutions of the present invention are further described below in conjunction with specific implementation examples, but the present invention is not limited thereto. Each example is prepared according to the above laboratory method.

[0052] Example 1

[0053] According to the mass fraction, 100 parts of recycled brick powder were placed in a 60℃ oven and dried for 24 hours, then fully stirred with 3 parts of ammonium chloride flux, and after stirring evenly, the mixed powder was placed in a muffle furnace and calcined at 200℃ for 6 hours to obtain alkali-melting activated recycled brick powder. 30 parts of water and 5 parts of sodium metasilicate alkali activator were mixed evenly to obtain solution 1; 60 parts of alkali-melting activated recycled brick powder and 40 parts of marble saw mud were added to the stirring pot, and stirred thoroughly to make the components fully mixed to obtain powder 1; then the powder 1 was mixed with solution 1 and continued to stir, first slowly stirred at a speed of 90r / min for 60s, paused for 15s, scraped off the slurry on the wall of the stirring pot, and continued to stir quickly at a speed of 250r / min for 60s; after the fast stirring was completed, the stirring speed was maintained at 100r / min and continued to stir for 30s. Until the components were evenly mixed, an alkali-melting activated recycled brick powder geopolymer slurry was obtained. The slurry was poured into a 20mm×20mm×20mm mold, demolded after 24 hours and cured under standard conditions for 28 days. The compressive strength was tested to be 25.47MPa.

[0054] Substitute the mix ratio data into the strength calculation formula, C is the 28d compressive strength of the alkali-melting activated recycled brick powder geopolymer, m s is the mass fraction of the precursor material, m f is the mass fraction of flux, m a is the mass fraction of the alkali activator, T is the calcination temperature, m w is the mass fraction of water, ∑m 固 is the total mass fraction of alkali melting activated regenerated brick powder, precursor material, and alkali activator. When the precursor material is marble saw mud, S 1 =1.1; when the flux is ammonium chloride, K 1 =1; when the alkaline activator is sodium metasilicate, K 2 =0.1; get

[0055]

[0056] It can be seen that the error between the strength calculation formula and the actual measured 28d compressive strength does not exceed 5%.

[0057] Example 2

[0058] According to the mass fraction, 100 parts of recycled brick powder were placed in a 60℃ oven and dried for 24 hours, then fully stirred with 5 parts of barium fluoride flux, and after stirring evenly, the mixed powder was placed in a muffle furnace and calcined at 200℃ for 6 hours to obtain alkali-melting activated recycled brick powder. 20 parts of water and 7 parts of potassium hydroxide alkaline activator were mixed evenly to obtain solution 1; 20 parts of alkali-melting activated recycled brick powder and 80 parts of metakaolin were added to the stirring pot, and stirred thoroughly to make the components fully mixed to obtain powder 1; then the powder 1 was mixed with solution 1 and continued to stir, first slowly stirred at a speed of 100r / min for 60s, paused for 15s, scraped off the slurry on the wall of the stirring pot, and continued to stir quickly at a speed of 260r / min for 60s; after the fast stirring was completed, the stirring speed was maintained at 100r / min and continued to stir for 30s. Until all components were evenly mixed, an alkali-melting activated recycled brick powder geopolymer slurry was obtained. The slurry was poured into a 20 mm × 20 mm × 20 mm mold, demolded after 24 hours and cured under standard conditions for 28 days. The compressive strength was tested to be 101.24 MPa.

[0059] Substitute the mix ratio data into the strength calculation formula, C is the 28d compressive strength of the alkali-melting activated recycled brick powder geopolymer, m s is the mass fraction of the precursor material, m f is the mass fraction of flux, m a is the mass fraction of the alkali activator, T is the calcination temperature, m w is the mass fraction of water, ∑m 固 is the total mass fraction of alkali-melting activated regenerated brick powder, precursor material, and alkali activator. When the precursor material is metakaolin, S 1 =1.12; when the flux is barium fluoride, K 1 =3; when the alkaline activator is potassium hydroxide, K 2 = 0.3, we get

[0060]

[0061] It can be seen that the error between the strength calculation formula and the actual measured 28d compressive strength does not exceed 5%.

[0062] Example 3

[0063] According to the mass fraction, 100 parts of recycled brick powder were placed in a 60℃ oven and dried for 24 hours, then fully stirred with 4 parts of lithium metaborate flux, and after stirring evenly, the mixed powder was placed in a muffle furnace and calcined at 200℃ for 6 hours to obtain alkali-melting activated recycled brick powder. 25 parts of water and 6 parts of potassium silicate alkali activator were mixed evenly to obtain solution 1; 40 parts of alkali-melting activated recycled brick powder and 60 parts of steel slag were added to the stirring pot, and stirred thoroughly to make the components fully mixed to obtain powder 1; then the powder 1 was mixed with solution 1 and continued to stir, first slowly stirring at a speed of 95r / min for 60s, pausing for 15s, scraping off the slurry on the wall of the stirring pot, and continuing to stir quickly at a speed of 255r / min for 60s; after the fast stirring was completed, the stirring speed was maintained at 100r / min and continued to stir for 30s. Until the components were evenly mixed, an alkali-melting activated recycled brick powder geopolymer slurry was obtained. The slurry was poured into a 20 mm × 20 mm × 20 mm mold, demolded after 24 hours and cured under standard conditions for 28 days. The compressive strength was tested to be 57.82 MPa.

[0064] Substitute the mix ratio data into the strength calculation formula, C is the 28d compressive strength of the alkali-melting activated recycled brick powder geopolymer, m s is the mass fraction of the precursor material, m f is the mass fraction of flux, m a is the mass fraction of the alkali activator, T is the calcination temperature, m w is the mass fraction of water, ∑m 固 is the total mass fraction of alkali-melting activated regenerated brick powder, precursor material, and alkali activator. When the precursor material is steel slag, S 1 =1.11; when the flux is lithium metaborate, K 1 =2; when the alkaline activator is potassium silicate, K 2 = 0.2, we get

[0065]

[0066] It can be seen that the error between the strength calculation formula and the actual measured 28d compressive strength does not exceed 5%.

[0067] Example 4

[0068] According to the mass fraction, 100 parts of recycled brick powder were placed in a 60℃ oven and dried for 24 hours, then fully stirred with 5 parts of barium fluoride flux, and after stirring evenly, the mixed powder was placed in a muffle furnace and calcined at 200℃ for 6 hours to obtain alkali-melting activated recycled brick powder. 30 parts of water and 5 parts of potassium silicate alkali activator were mixed evenly to obtain solution 1; 60 parts of alkali-melting activated recycled brick powder and 40 parts of metakaolin were added to the stirring pot, and stirred thoroughly to make the components fully mixed to obtain powder 1; then the powder 1 was mixed with solution 1 and continued to stir, first slowly stirred at a speed of 100r / min for 60s, paused for 15s, scraped off the slurry on the wall of the stirring pot, and continued to stir quickly at a speed of 260r / min for 60s; after the fast stirring was completed, the stirring speed was maintained at 100r / min and continued to stir for 30s. Until all components were evenly mixed, an alkali-melting activated recycled brick powder geopolymer slurry was obtained. The slurry was poured into a 20 mm × 20 mm × 20 mm mold, demolded after 24 hours and cured under standard conditions for 28 days. The compressive strength was tested to be 46.15 MPa.

[0069] Substitute the mix ratio data into the strength calculation formula, C is the 28d compressive strength of the alkali-melting activated recycled brick powder geopolymer, m s is the mass fraction of the precursor material, m f is the mass fraction of flux, m a is the mass fraction of the alkali activator, T is the calcination temperature, m w is the mass fraction of water, ∑m 固 is the total mass fraction of alkali-melting activated regenerated brick powder, precursor material, and alkali activator. When the precursor material is metakaolin, S 1 =1.12; when the flux is barium fluoride, K 1 =3; when the alkaline activator is potassium silicate, K 2 = 0.2, we get

[0070]

[0071] The error between the strength calculation formula and the actual measured 28d compressive strength does not exceed 5%.

[0072] Example 5

[0073] According to the mass fraction, 100 parts of recycled brick powder were placed in a 60℃ oven and dried for 24 hours, then fully stirred with 4 parts of ammonium chloride flux, and after stirring evenly, the mixed powder was placed in a muffle furnace and calcined at 200℃ for 6 hours to obtain alkali-melting activated recycled brick powder. 20 parts of water and 7 parts of potassium hydroxide alkaline activator were mixed evenly to obtain solution 1; 40 parts of alkali-melting activated recycled brick powder and 60 parts of steel slag were added to the stirring pot, and stirred thoroughly to make the components fully mixed to obtain powder 1; then the powder 1 was mixed with solution 1 and continued to stir, first slowly stirred at a speed of 100r / min for 60s, paused for 15s, scraped off the slurry on the wall of the stirring pot, and continued to stir quickly at a speed of 260r / min for 60s; after the fast stirring was completed, the stirring speed was maintained at 100r / min and continued to stir for 30s. Until the components were evenly mixed, an alkali-melting activated recycled brick powder geopolymer slurry was obtained. The slurry was poured into a 20 mm × 20 mm × 20 mm mold, demolded after 24 hours and cured under standard conditions for 28 days. The compressive strength was tested to be 50.69 MPa.

[0074] Substitute the mix ratio data into the strength calculation formula, C is the 28d compressive strength of the alkali-melting activated recycled brick powder geopolymer, m s is the mass fraction of the precursor material, m f is the mass fraction of flux, m a is the mass fraction of the alkali activator, T is the calcination temperature, m w is the mass fraction of water, ∑m 固 is the total mass fraction of alkali-melting activated regenerated brick powder, precursor material, and alkali activator. When the precursor material is steel slag, S 1 =1.11; when the flux is ammonium chloride, K 1 =1; when the alkaline activator is potassium hydroxide, K 2 = 0.3, we get

[0075]

[0076] The error between the strength calculation formula and the actual measured 28d compressive strength does not exceed 5%.

[0077] Example 6

[0078] According to the mass fraction, 100 parts of recycled brick powder were placed in a 60℃ oven and dried for 24 hours, then fully stirred with 3 parts of ammonium chloride flux, and after stirring evenly, the mixed powder was placed in a muffle furnace and calcined at 200℃ for 6 hours to obtain alkali-melting activated recycled brick powder. 25 parts of water and 6 parts of potassium hydroxide alkaline activator were mixed evenly to obtain solution 1; 60 parts of alkali-melting activated recycled brick powder and 40 parts of marble saw mud were added to the stirring pot, and stirred thoroughly to make the components fully mixed to obtain powder 1; then the powder 1 was mixed with solution 1 and continued to stir, first slowly stirred at a speed of 90r / min for 60s, paused for 15s, scraped off the slurry on the wall of the stirring pot, and continued to stir quickly at a speed of 250r / min for 60s; after the fast stirring was completed, the stirring speed was maintained at 100r / min and continued to stir for 30s. Until the components were evenly mixed, an alkali-melting activated recycled brick powder geopolymer slurry was obtained. The slurry was poured into a 20 mm × 20 mm × 20 mm mold, demolded after 24 hours and cured under standard conditions for 28 days. The compressive strength was tested to be 31.75 MPa.

[0079] Substitute the mix ratio data into the strength calculation formula, C is the 28d compressive strength of the alkali-melting activated recycled brick powder geopolymer, m s is the mass fraction of the precursor material, m f is the mass fraction of flux, m a is the mass fraction of the alkali activator, T is the calcination temperature, m w is the mass fraction of water, ∑m 固 is the total mass fraction of alkali melting activated regenerated brick powder, precursor material, and alkali activator. When the precursor material is marble saw mud, S 1 =1.1; when the flux is ammonium chloride, K 1 =1; when the alkaline activator is potassium hydroxide, K 2 =0.3; get

[0080]

[0081] The error between the strength calculation formula and the actual measured 28d compressive strength does not exceed 5%.

[0082] Example 7

[0083] According to the mass fraction, 100 parts of recycled brick powder were placed in a 60℃ oven and dried for 24 hours, then fully stirred with 3 parts of ammonium chloride flux, and after stirring evenly, the mixed powder was placed in a muffle furnace and calcined at 200℃ for 6 hours to obtain alkali-melting activated recycled brick powder. 20 parts of water and 5 parts of potassium silicate alkali activator were mixed evenly to obtain solution 1; 40 parts of alkali-melting activated recycled brick powder and 60 parts of metakaolin were added to the stirring pot, and stirred thoroughly to make the components fully mixed to obtain powder 1; then the powder 1 was mixed with solution 1 and continued to stir, first slowly stirred at a speed of 90r / min for 60s, paused for 15s, scraped off the slurry on the wall of the stirring pot, and continued to stir quickly at a speed of 250r / min for 60s; after the fast stirring was completed, the stirring speed was maintained at 100r / min and continued to stir for 30s. Until the components were evenly mixed, an alkali-melting activated recycled brick powder geopolymer slurry was obtained. The slurry was poured into a 20 mm × 20 mm × 20 mm mold, demolded after 24 hours and cured under standard conditions for 28 days. The compressive strength was tested to be 50.95 MPa.

[0084] Substitute the mix ratio data into the strength calculation formula, C is the 28d compressive strength of the alkali-melting activated recycled brick powder geopolymer, m s is the mass fraction of the precursor material, m f is the mass fraction of flux, m a is the mass fraction of the alkali activator, T is the calcination temperature, m w is the mass fraction of water, ∑m 固 is the total mass fraction of alkali-melting activated regenerated brick powder, precursor material, and alkali activator. When the precursor material is metakaolin, S 1 =1.12; when the flux is ammonium chloride, K 1 =1; when the alkaline activator is potassium silicate, K 2 =0.2; get

[0085]

[0086] It can be seen that the error between the strength calculation formula and the actual measured 28d compressive strength does not exceed 5%.

[0087] The mix ratio design of an alkali-melting activated recycled brick powder geopolymer of the present invention adopts the recycled brick powder after alkali-melting activation as the raw material to prepare the geopolymer. After being excited by an alkali activator, its 28d maximum strength can reach 101.24MPa. The 28d strength of the traditional recycled brick powder geopolymer is 30MPa, which is much lower than the 28d strength of the present invention. In addition, the present invention is simple to operate, not only realizing the resource utilization of waste building brick powder, but also successfully preparing a cementitious material with high-strength characteristics. In addition, the present invention also provides an accurate calculation method for the strength of alkali-melting activated recycled brick powder geopolymer. The prediction accuracy of this calculation method in practical application is extremely high, and the error between the actual measured strength and the calculated strength does not exceed 5%. This calculation method can effectively predict the strength development trend of alkali-melting activated recycled brick powder geopolymer, providing reliable technical support for practical engineering applications, and has significant application value.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. An alkali-melting activated recycled brick powder geopolymer, characterized in that: It includes the following components by weight: 20-30 parts of water, 20-60 parts of alkali-melting activated regenerated brick powder, 40-80 parts of precursor material, 5-7 parts of alkali activator; Wherein, the alkali-melting activated regenerated brick powder is prepared by the following steps: Step a1: drying the recycled brick powder in an oven, and then grinding the recycled brick powder until the particle size of the recycled brick powder meets the requirements; Step a2: mixing the ground recycled brick powder with a flux, stirring the mixture evenly, calcining the mixture, and naturally cooling the mixture to obtain the alkali-melting activated recycled brick powder.

2. The alkali-melting activated recycled brick powder geopolymer according to claim 1, characterized in that: In step a1, the flux is 3-5 parts by mass, the recycled brick powder is 20-60 parts by mass, the drying temperature in the oven is 60° C., the time is at least 24 hours, and the particle size requirement is not greater than 0.2 mm.

3. The alkali-melting activated recycled brick powder geopolymer according to claim 1, characterized in that: In step a2, during the calcination process, the sample is placed in a muffle furnace and calcined at 200° C. for 6 hours with a heating rate of 20° C. / min.

4. The alkali-melting activated recycled brick powder geopolymer according to claim 1, characterized in that: The flux is one of lithium metaborate, barium fluoride and ammonium chloride, and its mass concentration is 20%-40%.

5. The alkali-melting activated recycled brick powder geopolymer according to claim 1, characterized in that: The silicon dioxide content in the recycled brick powder is not less than 45%.

6. The alkali-melting activated recycled brick powder geopolymer according to claim 1, characterized in that: The precursor material is one of marble saw mud, steel slag and metakaolin, and the calcium content of the precursor material is not less than 40%.

7. The alkali-melting activated recycled brick powder geopolymer according to claim 1, characterized in that: The alkaline activator is one of potassium hydroxide, potassium silicate and sodium metasilicate, and its mass concentration is 20%-40%.

8. A method for preparing an alkali-melting activated recycled brick powder geopolymer as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Mix water and alkaline activator evenly to obtain a mixed solution; Adding the alkali-melting activated regenerated brick powder and the precursor material into a stirring pot, mixing and stirring them thoroughly to obtain a mixed powder; Step 2: Mix and stir the mixed powder and the mixed solution to finally obtain an alkali-melting activated recycled brick powder geopolymer.

9. The method for preparing the alkali-melting activated regenerated brick powder geopolymer according to claim 8, characterized in that: During the mixing and stirring of the mixed powder and the mixed solution: Stir slowly for 60 seconds, pause for 15 seconds, scrape the slurry off the wall of the stirring pot, continue to stir quickly for 60 seconds, and finally stir slowly for 30 seconds; The stirring speeds of the slow stirring and the fast stirring are 90-100 r / min and 250-260 r / min respectively.

10. A strength calculation method for alkali-melting activated recycled brick powder geopolymer according to any one of claims 1 to 7, characterized in that: The formula for strength calculation method is: Where: C is the 28d compressive strength of alkali-melting activated recycled brick powder geopolymer, m s is the mass fraction of the precursor material, m f is the mass fraction of flux, m a is the mass fraction of the alkali activator, T is the calcination temperature, m w is the mass fraction of water, ∑m 固 is the total mass fraction of alkali-melting activated recycled brick powder, precursor material and alkali activator; S1, K1 and K2 are correction factors of precursor material, flux and alkali activator respectively, and the values ​​depend on the specific types of precursor material, flux and alkali activator.

Citation Information

Patent Citations

  • Regenerated micro-powder lightweight aggregate and preparation method thereof

    CN106167395A

  • Foamed slag-based geopolymer material and preparation method thereof

    CN110526632A

  • Method for preparing geopolymer cementing material from regenerated micro-powder

    CN111138104A

  • Alkali-activated regenerated clay brick powder cementing material as well as preparation method and application thereof

    CN113149547A

  • Method for preparing photocatalyst by regenerating and recycling waste SCR (Selective Catalytic Reduction) denitration catalyst and photocatalyst

    CN113877589A